Incorporation of hydrogen‐bonding units into polymeric semiconductors toward boosting charge mobility, intrinsic stretchability, and self‐healing ability. (2nd September 2021) - Yu, Xiaobo; Li, Cheng; Gao, Chenying; Zhang, Xisha; Zhang, Guanxin; Zhang, Deqing
Abstract: The soft nature has endowed conjugated polymers with promising applications in a wide range of field‐effect transistor (FET) based flexible electronics. With unremitting efforts on revealing the molecular structure–property relationships, numerous novel conjugated polymers with high mobility and excellent mechanical property have been developed in the past decades. Incorporating hydrogen‐bonding (H‐bonding) units into semiconducting polymers is one of the most successful strategies for designing high‐performance semiconducting materials. In this review, we aim to highlight the roles of H‐bonding units in the performances of polymeric FETs from three aspects. These include (i) charge mobility enhancement for semiconducting polymers after incorporation of H‐bonding units into the side chains, (ii) the effects of H‐bonding units on the stretchability of conjugated polymers, and (iii) the improvement of self‐healing properties of conjugated polymers containing dynamic hydrogen bonds due to the H‐bonding units in the side chains or conjugated backbones. Abstract : In this review, the effects of H‐bonding units on the interchain packing order, semiconducting performance, stretchability and self‐healing property of conjugated polymers have been summarized and discussed.